INCREASING MANAGEMENT EFFICIENCY IN THE FOOD INDUSTRY GRAIN PRODUCTS NETWORK IN THE CONDITIONS OF THE DIGITAL ECONOMY: THEORETICAL AND METHODOLOGICAL APPROACH (Marketing Journal, 2025)
This article explores the theoretical and methodological foundations for improving management efficiency in the grain processing sector of the food industry 325 under the conditions of digital transformation. The study examines how classical management approaches are evolving through the integration of digital technologies. Five key areas are highlighted: strategic planning, operational management, risk management , quality control, and human resources. The paper compares Uzbekistan’s experience with international best practices. Special emphasis is placed on the role of ERP systems, business intelligence tools, artificial intelligence, and the Internet of Things in enhancing decision -making. A four -level comprehensive model for improving management efficiency is proposed, based on systematic and phased development.
Keywords: management efficiency; digital transformation; strategic management; operational control; grain sector; artificial intelligence; risk management; quality management